1975
DOI: 10.1128/aac.7.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Clinical Isolates of Enterobacteriaceae to BL-S640, a New Oral Cephalosporin

Abstract: The in vitro activity of BL-S640, a 7-(2-aryl-2-aminoacetamido)-3-(heterocyclic-thiomethyl) cephalosporin, was evaluated against 338 clinical isolates of Enterobacteriaceae in comparison with ampicillin, cephalothin, cefazolin, and cephalexin. Against Escherichia coli, BL-S640 was as active as cefazolin and more active than ampicillin, cephalothin, and cephalexin. BL-S640 was as effective as the other cephalosporins tested and far more active than ampicillin against Klebsiella and was more active than cephalex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…However, recently a number of new cephalosporins have been synthesized that seem to have a markedly broader spectrum against gram-negative bacilli. Among the most promising are cefamandole (2,4,5,7,10), cefuroxime (5,11,12), cefatrizine (6,7,13,15), cefoxitin (3, 7-9, 11, 14), and cefazaflur (SKF 59962) (1).…”
mentioning
confidence: 99%
“…However, recently a number of new cephalosporins have been synthesized that seem to have a markedly broader spectrum against gram-negative bacilli. Among the most promising are cefamandole (2,4,5,7,10), cefuroxime (5,11,12), cefatrizine (6,7,13,15), cefoxitin (3, 7-9, 11, 14), and cefazaflur (SKF 59962) (1).…”
mentioning
confidence: 99%
“…coli and Klebsiella were inhibited by low concentrations (<8 ,ug/ml) of BL-S640: 81% of E. coli and 70% of K. pneumoniae tested. As predicted, based on previous studies by other workers (5,8,10,11), Serratia and Pseudomonas species were uniformly resistant to >128 ,g of each of the cephalosporins per ml.…”
Section: Resultsmentioning
confidence: 76%
“…A similar situation was found with an Acinetobacter isolate. DISCUSSION Earlier publications (1,2,6,8,9) have suggested that cefatrizine is an agent that would extend the spectrum of oral and parenteral cephalosporins, but these studies compared its activity with that of older agents and not with that of cefamandole, cefuroxime, and cefoxitin, which have an expanded spectrum of activity (3)(4)(5). Although cefatrizine has excellent stability com- …”
Section: Resultsmentioning
confidence: 99%